Analisis Fiqih Muamalah Terhadap Penerapan Sistem Pembayaran Cicilan (PayLater) Pada Marketplace Shopee - Nasywa Salma Saidah; Rifa RihhadatulAisya; Muhibban (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Rapid technological advances have given birth to various kinds of brave shopping applications, one of which is Shopee, which is one of the most popular platforms in society. Shopee offers various payment methods, including installment payments known as Shopee PayLater. This research aims to determine and analyze the practice of using Shopee PayLater based on the perspective of Sharia Economic Law. This research uses a qualitative approach with descriptive-analytical methods to produce Shopee PayLater transactions. The research results show that the Shopee PayLater payment method is not permitted under Sharia Economic Law because it contains elements of usury. Debt and receivable transactions between users and Shopee involve interest or benefits received by Shopee, which is recommended as Riba Qardh. Apart from that, the application of fines for late payment of PayLater bills is also not in accordance with sharia principles because there is an additional nominal amount when paying the fine, which is categorized as Usury Jahiliah. Thus, the Shopee PayLater practice is considered haram from the perspective of Sharia Economic Law.